Ky Fan minimax inequalities for set-valued mappings - Zhang, Yu; Li, Sheng-Jie (Fixed point theory and algorithms for sciences and engineering, 2012)
In this article, by virtue of the Kakutani-Fan-Glicksberg fixed point theorem, two types of Ky Fan minimax inequalities for set-valued mappings are obtained. Some examples are given to illustrate our results. Mathematics Subject Classification (2010) : 49J35; 49K35; 90C47.